Improving productivity in an SME in the metalworking sector through lean manufacturing and TPM tools: a case study in Peru - Huaman Echevarria, Christian Elian (2024)
This research develops the validation of an operations model that aims to mitigate the root causes of low productivity within a company that offers sandblasting and painting services for metal structures in Lima. It can also be confirmed that Lean Manufacturing tools optimize the processes of SMEs in the service sector; the implementation of these tools yields positive results in the long term. Not only does it improve the quality of service, but it also enhances the organizational culture within these companies. In this case study, an integrated model was used that incorporates Lean Manufacturing tools, including preventive and autonomous maintenance, 5S, and SMED, to address the main problem. The 5S provided adequate classification, organization, cleanliness, discipline, and standardization within the workstations. SMED reduced machine setup times for painting by eliminating non-value-added activities in the process. Additionally, by incorporating two pillars of TPM—preventive and autonomous maintenance—a maintenance program was implemented, which ultimately resulted in reduced painting machine setup times. For the implementation of these tools, pilot tests were conducted for each of them. The findings validated a 10% improvement in productivity and a 23.8% increase in efficiency. Furthermore, a 32.04% reduction in setup time was observed.